Construct Validation of Organizational Citizenship Behaviour in an Asian Context : An Evidence among Academicians in Private Universities in Pakistan - Asif Ayub, Kiyani; Kartinah, binti Ayupp; Shahid, Rasool (Universiti Putra Malaysia Press, 2019)
The objectives of the research study were to explore the factorial structure and to establish validities of organizational citizenship behaviour among academicians’ working in private universities in Pakistan. Purposive sampling and quota sampling were used for allocating samples of 347 academicians to 21 private universities in the Punjab/ Islamabad Capital Territory of Pakistan. Organizational citizenship behaviour consisted of seven items and after exploratory factor analysis all items loaded strongly on one component and were labelled as “Organizational Citizenship Behaviour”. The instrument of organizational citizenship behaviour was validated in the Pakistan’s context. The one factor solution for the organizational citizenship behaviour construct was also confirmed through PLS (SEM). This study is unique in validating empirically the instruments of Organizational citizenship behaviour in Pakistan’s (Asian) context among academicians in private higher education industry. Moreover, because of validated factorial validities of organizational citizenship behaviour researcher can academically differentiate between the factor structure of task performance and organizational citizenship behaviour among academicians in private higher education .